ENHANCING INNOVATIVE BEHAVIOR THROUGH STRENGTHENING SELF-EFFICACY, TEAMWORK, ORGANIZATIONAL SUPPORT, AND ORGANIZATIONAL COMMITMENT - Irwan Siagian; Rita Retnowati; Eka Suhardi; Nurma Tambunan (JF Publisher, 2025)
This research addresses the critical need to enhance innovative behavior among private vocational school teachers in Depok City, focusing on the interplay of self-efficacy, teamwork, organizational support, and organizational commitment. Despite existing studies on these variables, a gap remains in understanding their collective impact on fostering innovation in educational settings. The primary purpose of this research is to explore further how these factors contribute to teachers' innovative behavior, thereby providing insights for educational management. In order to achieve this, a field survey method was employed, gathering data from teachers to analyze the relationships between self-efficacy, teamwork, organizational support, and organizational commitment on innovative behavior. The findings of the research reveal that self-efficacy significantly influences organizational commitment, with coefficients indicating positive relationships: self-efficacy (0.131), teamwork (0.184), and organizational support (0.361). Furthermore, the research establishes that self-efficacy indirectly enhances innovative behavior through organizational commitment, highlighting the importance of fostering a supportive environment for teachers.